Contribution of managed honeybees (Apis mellifera scutellata Lep.) to sunflower (Helianthus annuus L.) seed yield and quality - Pirk, Christian Walter Werner (University of Pretoria, 2013)
Dissertation (MScAgric)--University of Pretoria, 2010.